Evaluation of isotretinoin gel and oral zinc sulphate in the treatment of plane warts - Fadheel, Basman M.; Salih, Hayder R.; AL-waaiz, Mukram M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Plane warts represent a common dermatological problem encountered in daily practice with no uniformly effective treatment modality. Patients and methods: This study was conducted at the Department of Dermatology and Venereology of Baghdad Teaching Hospital / Medical City from April 2005 to June 2006. Fifty patients enrolled in the study and 36 completed it. Patients were instructed to apply isotretinoin gel once daily and keep on regular follow up every 2 weeks for one month to assess the esponse and side effects. At the end of the first month those with complete cure were instructed to stop therapy and keep on regular follow up to detect any recurrence.Patients with no response were divided into 2 groups. One group continued on isotretinoin gel alone. In the second group oral zinc sulphate was added and both groups were reevaluated after one month. Results: 22patients out of 36 (61.7%) showed complete cure after one month of isotretinoin gel therapy. In the group that continued on isotretinoin gel for another month cure rate was 42.8% (3 patients out of 7) while in the other group where oral zinc sulphate was added the cure rate was 71.4% (5 patients out of 7).The total number of patients with complete cure throughout the study was 30 patients (83.3%).The results also showed that the cure rate for warts located on the face is much higher than cure rate for those located in the limbs and hands. Conclusions: The result of this study showed that isotretinoin gel is a new effective and well tolerated therapy for the treatment of plane warts.Adding oral zinc sulphate seems to increase the cure rate especially for those patients who did not respond to isotretinoin.